2001
DOI: 10.1128/mcb.21.24.8398-8413.2001
|View full text |Cite
|
Sign up to set email alerts
|

TIP49b, a Regulator of Activating Transcription Factor 2 Response to Stress and DNA Damage

Abstract: Activating transcription factor 2 (ATF2/CRE-BP1) is implicated in transcriptional control150-248 in fibroblasts or melanoma but not in ATF2-null cells caused a profound G 2 M arrest and increased degree of apoptosis following irradiation. The interaction between ATF2 and TIP49b constitutes a novel mechanism that serves to limit ATF2 transcriptional activities and highlights the central role of ATF2 in the control of the cell cycle and apoptosis in response to stress and DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 70 publications
2
72
0
1
Order By: Relevance
“…9 Several publications have shown that RUVBL2 behaves as an antagonist of the transcriptional activity of the ␤-catenin-T-cell factor/lymphoid enhancer-binding factor complex. 9,15 Because ␤-catenin is considered an oncogene in HCC, these results appear counterintuitive. However, recently, RUVBL2 was also found to be required for the repressing effect of ␤-catenin on the transcription of the antimetastatic gene KAI-1, 36 which is frequently down-regulated in HCC.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…9 Several publications have shown that RUVBL2 behaves as an antagonist of the transcriptional activity of the ␤-catenin-T-cell factor/lymphoid enhancer-binding factor complex. 9,15 Because ␤-catenin is considered an oncogene in HCC, these results appear counterintuitive. However, recently, RUVBL2 was also found to be required for the repressing effect of ␤-catenin on the transcription of the antimetastatic gene KAI-1, 36 which is frequently down-regulated in HCC.…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, RUVBL2 has been found in supramolecular complexes that do not include ␤-catenin, 11 and ␤-catenin-independent functions of RUVBL2 have already been identified. 15 It is also noteworthy that RUVBL2 is required for the viability of yeast, 7,31,32 an organism devoid of ␤-catenin. In this context, 1 of the salient findings of this study was that in addition to its overexpression in HCC, RUVBL2 was also found in the cytoplasm of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, treatment with TBEP altered the expression of proteins related to DNA damage and caused an increase in the number of apoptotic cells in the tail region. Previous studies demonstrated that RuvB-like (RBL) proteins play a key role in modulating the response to DNA damage (Cho et al, 2001;Kakugawa et al, 2009), and exposure to TBEP significantly downregulated the expression of Rbl2 in this study. Thus, this downregulation may inhibit the biological response to DNA damage, which was supported by downregulated expression of proteins related to DNA repair (DEAH (Asp-Glu-Ala-His) box polypeptide 15, and protein BCCIP homolog).…”
Section: Discussionmentioning
confidence: 62%
“…With regard to Reptin, the Walker B mutant D299N was not able to complement the effect of the loss of endogenous Reptin on the amount of PIKK proteins in HEK293 cells (7), suggesting that the ATPase activity of Reptin is indeed required for the regulation of PIKK levels. However, the same mutant was as efficient as wild-type (WT) Reptin for the repression of the influenza A virus polymerase (18) or of the transcriptional activity of ATF2 (19). In the latter case, the C-terminus part of Reptin lacking both Walker domains was almost as efficient as the complete protein.…”
Section: Introductionmentioning
confidence: 90%